2017
DOI: 10.3390/ijms18050952
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Dimethyllirioresinol, Epimagnolin A, Eudesmin, Fargesin, and Magnolin on Cytochrome P450 Enzyme Activities in Human Liver Microsomes

Abstract: Magnolin, epimagnolin A, dimethyllirioresinol, eudesmin, and fargesin are pharmacologically active tetrahydrofurofuranoid lignans found in Flos Magnoliae. The inhibitory potentials of dimethyllirioresinol, epimagnolin A, eudesmin, fargesin, and magnolin on eight major human cytochrome P450 (CYP) enzyme activities in human liver microsomes were evaluated using liquid chromatography-tandem mass spectrometry to determine the inhibition mechanisms and inhibition potency. Fargesin inhibited CYP2C9-catalyzed diclofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Epimagnolin (Figure 1A), a natural lignan compound abundantly found in Magnolia flos, has a very similar chemical structure to those of magnolin 29 and aschantin. 30 Our previous studies demonstrated that magnolin and aschantin suppressed tumor promoter-induced carcinogenesis and cancer cell proliferation.…”
Section: Epimagnolin Suppresses Cell Proliferation By Inhibition Ofmentioning
confidence: 99%
“…Epimagnolin (Figure 1A), a natural lignan compound abundantly found in Magnolia flos, has a very similar chemical structure to those of magnolin 29 and aschantin. 30 Our previous studies demonstrated that magnolin and aschantin suppressed tumor promoter-induced carcinogenesis and cancer cell proliferation.…”
Section: Epimagnolin Suppresses Cell Proliferation By Inhibition Ofmentioning
confidence: 99%
“…Previously, fargesin from the Magnolia plants which are used in the treatment of headache, nasal congestion and sinusitis was shown to improve dyslipidemia and hyperglycemia in high fat-induced obese mice by phosphorylating and activating Akt, AMP-activated protein kinase (AMPK), and acetyl-CoA carboxylase in both 3T3-L1 adipocytes and white adipose tissue (Lee et al 2012 ). In addition, in vitro inhibitory activities of fargesin from Flos Magnoliae on eight different cytochrome P450 enzymes were determined suggesting that fargesin may modulate drug metabolism, but more in vivo studies are required to investigate drug interactions (Kim et al 2017 ). A recent study showed that fargesin inhibits atherosclerosis by promoting reverse cholesterol transport process and reduced inflammatory response via CEBPαS21/LXRα and TLR4/NF-κB pathways (Wang et al 2020 ) Similarly, alteration of CYP46A1 and HMG-CoA reductase on Lipopolysaccharide stimulation through TLR4/MyD88/NF-κB signalling pathway leading to neuroinflammation has been reported (Na et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of yangambin, epimagnolin A, eudesmin, fargesin, and magnolin on CYP activities in human liver microsomes were previously investigated [ 30 ]. Fargesin inhibited competitively CYP2C9-catalyzed diclofenac 4′-hydroxylation ( K i , 16.3 μM) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effects of yangambin, epimagnolin A, eudesmin, fargesin, and magnolin on CYP activities in human liver microsomes were previously investigated [ 30 ]. Fargesin inhibited competitively CYP2C9-catalyzed diclofenac 4′-hydroxylation ( K i , 16.3 μM) [ 30 ]. It also exhibited the time-dependent inhibition of CYP2C8 ( K i : 10.7 µM and k inact : 0.082 min −1 ), CYP2C19 ( K i : 3.7 µM and k inact : 0.102 min −1 ), and CYP3A4 ( K i : 23.0 µM and k inact : 0.050 min −1 ) in human liver microsomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation